Therapeutic Procedures and Use of Alternating Antipyretic Drugs for Fever Management in Children - Gracian Li Pereira; Noemia U.L. Tavares; Sotero S. Mengue; Tatiane da S. Dal Pizzol (Elsevier, 2013)
Objective: The evidence on the effectiveness of alternating antipyretics in fever management is scarce and indicates clinically negligible differences. The present study aimed to describe therapeutic procedures and the use of alternating antipyretics in children, and to evaluate associated factors. Methods: This was a cross-sectional study with 692 children aged 0 to 6 years, living in Southern Brazil. Household interviews of the children's caregivers were conducted through cluster sampling using a structured questionnaire. A descriptive analysis was carried out, and the association between the use of alternating antipyretics and sociodemographic factors was evaluated. A total of 630 cases were analyzed (91.0%), corresponding to children with a history of fever. Results: Approximately 73% of caregivers reported that the first measure adopted during the last fever episode was the administration of medication. The mean temperature considered as fever by caregivers was 37.4 °C, and as high fever, 38.7 °C. The use of alternating antipyretic therapy was reported by 26.7% of respondents, justified by the lack of response to monotherapy and medical indication, in most cases. The drugs most often used were dipyrone and paracetamol. Children whose primary caregiver was a parent with higher socioeconomic status and higher educational level received more alternating medications. Approximately 70% of the doses used were below the minimum recommended dose for the treatment of fever. Conclusions: The use of medication to control fever is a common practice, including alternating antipyretic regimens. Most caregivers consider as fever temperatures lower than those established and they reported lack of response to monotherapy and medical indication as the main reasons for alternating medication. Resumo: Objetivo: As evidências sobre a eficácia do uso alternado de antitérmicos no manejo da febre são escassas e apontam diferenças clinicamente desprezíveis. O objetivo do estudo foi descrever condutas terapêuticas e uso alternado de antipiréticos em crianças, e avaliar fatores associados ao uso alternado. Métodos: Estudo transversal com 692 crianças de zero a seis anos, residentes no Sul do Brasil. Por meio de amostragem por conglomerados, foram realizadas entrevistas domiciliares com os cuidadores, utilizando questionário estruturado. Foi realizada análise descritiva e avaliada a associação entre o uso alternado de antipiréticos e fatores sociodemográficos. Foram analisados 630 casos (91,0%), correspondendo às crianças com histórico de febre. Resultados: Cerca de 73% dos cuidadores informaram que a primeira medida adotada no último episódio de febre foi administrar medicamentos. A média de temperatura considerada febre foi de 37,4 °C, e febre alta, 38,7 °C. A utilização de terapia alternada com antipiréticos foi relatada por 26,7% dos entrevistados, justificada pela ausência de resposta à monoterapia e indicação médica, na maioria dos casos. Os medicamentos mais utilizados foram dipirona e paracetamol. Crianças cujo principal cuidador era um dos pais, com melhores condições socioeconômicas e maior nível educacional, receberam mais medicamentos alternados. Cerca de 70% das doses utilizadas estavam abaixo da dose mínima recomendada para tratamento de febre. Conclusões: O uso de medicamentos para controlar a febre é uma prática comum, incluindo esquemas alternados de antipiréticos. A maioria dos cuidadores considera como febre temperaturas inferiores às preconizadas, e apontou não resposta à monoterapia e indicação médica como as principais razões para o uso alternado. Keywords: Fever, Children, Treatment, Alternating therapy, Antipyretics, Palavras-chave: Febre, Crianças, Tratamento, Terapia alternada, Antipiréticos